Image Regions Contributing to Perceptual Translucency: A Psychophysical Reverse-Correlation Study. (September 2013) - Nagai, Takehiro; Ono, Yuki; Tani, Yusuke; Koida, Kowa; Kitazaki, Michiteru; Nakauchi, Shigeki
The spatial luminance relationship between shading patterns and specular highlight is suggested to be a cue for perceptual translucency (Motoyoshi, 2010 ). Although local image features are also important for translucency perception (Fleming & Bulthoff, 2005 ), they have rarely been investigated. Here, we aimed to extract spatial regions related to translucency perception from computer graphics (CG) images of objects using a psychophysical reverse-correlation method. From many trials in which the observer compared the perceptual translucency of two CG images, we obtained translucency-related patterns showing which image regions were related to perceptual translucency judgments. An analysis of the luminance statistics calculated within these image regions showed that (1) the global rms contrast within an entire CG image was not related to perceptual translucency and (2) the local mean luminance of specific image regions within the CG images correlated well with perceptual translucency. However, the image regions contributing to perceptual translucency differed greatly between observers. These results suggest that perceptual translucency does not rely on global luminance statistics such as global rms contrast, but rather depends on local image features within specific image regions. There may be some "hot spots" effective for perceptual translucency, although which of many hot spots are used in judging translucency may be observer dependent.